O Rio Mossoró e a educação ambiental na percepção de estudantes surdos - Souza, Niascara Valesca do Nascimento (Universidade Federal Rural do Semi-Árido, 2016)
This research comes to stimulate pro-environmental behaviour in a given group of deaf people. To achieve this goal, it is very important getting to know their imaginary with respect to environmental issues which take part of their everyday living. On being so, this thesis aims at verifying social representation of deaf students enrolled in the Elementary School, in the High School, and in the College, concerning to the Public Education in the town of Mossoró, in the State of Rio Grande do Norte about the Mossoró River pollution and its implication in relation to the environment. This research will be based on qualitative, descriptive, and explanatory method types over the environmental issue concerned to the Mossoró River. As research techniques, this study will rely on questionnaires with deaf students enrolled in the Teaching Institutions before mentioned. Afterwards, sign will be made in the LIBRAS (Brazilian Sign Language), in order to write up a glossary pertaining to the Environmental Sciences area. Data analysis will proceed, as it follows: data decoding, open comparative analysis, and grouping analysis. One can find so far: need of sign making in the LIBRAS, in relation to environmental area, as well as come up with a diagnosis over the deaf student knowledge about the Mossoró River pollution. At the end of the data collection the information was analysed and it was perceived that the majority of the deaf students had little knowledge of the issues related to the environmental area and one of the reasons for that was the lack of specif lexicon in LIBRAS and that is the reason why it was started a process of creation and validation of 20 signs respecting the linguistic aspects of the LIBRAS and the needs of the local deaf community. The understanding of new signs made it possible for deaf students to have access to up-to-date discussions in the environmental area and thus, it has positive implications in education (Elementary and Undergraduate) both in the Inclusive Education model and in the Bilingual Education model
The Mossoró River and environmental education in deaf students perception
Keywords: Libras; Criação de Sinais; Identidade Surda; Libras; Sign Creation; Deaf identity; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE